2007
DOI: 10.1128/jb.00899-06
|View full text |Cite
|
Sign up to set email alerts
|

Weak Rolling Adhesion Enhances Bacterial Surface Colonization

Abstract: Bacterial adhesion to and subsequent colonization of surfaces are the first steps toward forming biofilms, which are a major concern for implanted medical devices and in many diseases. It has generally been assumed that strong irreversible adhesion is a necessary step for biofilm formation. However, some bacteria, such as Escherichia coli when binding to mannosylated surfaces via the adhesive protein FimH, adhere weakly in a mode that allows them to roll across the surface. Since single-point mutations or even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 58 publications
(62 reference statements)
3
61
1
1
Order By: Relevance
“…It also might prove to be a significant disadvantage in other compartments critical for populational stability of E. coli, where the shear level is relatively high. For example, recently it has been shown that strong and firm 1M binding inhibits the spread of developing E. coli biofilms under flow conditions (1).…”
Section: Resultsmentioning
confidence: 99%
“…It also might prove to be a significant disadvantage in other compartments critical for populational stability of E. coli, where the shear level is relatively high. For example, recently it has been shown that strong and firm 1M binding inhibits the spread of developing E. coli biofilms under flow conditions (1).…”
Section: Resultsmentioning
confidence: 99%
“…Although the details of the conformational link between the interdomain configuration and the binding site are unclear, the allosteric properties of FimH are strongly supported by the presence in FimH of an integrin-like ligand-induced binding site epitope for monoclonal antibodies and by single-molecule studies using AFM (28). This catch bond mechanism was shown to provide a means for resistance of bacterial adhesion to soluble inhibitors and for surface spreading in biofilm formation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial adhesion and subsequent colonization of surfaces are the first step toward biofilm formation. Biofilm consisted of microcolonies encased in extracellular polysaccharide material which formed under selected conditions (Olson et al, 2002;Anderson et al, 2007). The biofilm develops on both living surfaces and artificial implants which allow the bacteria to persist for long period by establishment of dormant reservoir of pathogens, re-emergence of bacteria from this reservoir might be the source of recurrent infection (Deleo et al, 2010).…”
Section: Biofilm Formationmentioning
confidence: 99%